2014
DOI: 10.3390/ijms151223571
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-Encapsulating Small-Sized Polymeric Micelles with Higher Permeability and Its Efficacy on the Orthotopic Transplantation Model of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) elicits a dense stromal response that blocks vascular access because of pericyte coverage of vascular fenestrations. In this way, the PDAC stroma contributes to chemotherapy resistance, and the small-sized nanocarrier loaded with platinum has been adopted to address this problem which is not suitable for loading docetaxel (DTX). In the present study, we used the poly(d,l-lactide)-b-polyethylene glycol-methoxy (mPEG-b-PDLLA) to encapsulate DTX and got a small-sized polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…presented a similar approach for the fabrication of PEG ‐b‐ PDLLA small‐sized polymeric micelles with maleimide functional handles, which were subsequently conjugated to TAT peptides. Their in vitro and in vivo studies showed effectiveness and permeation higher than or similar to unfunctionalized cargo‐containing micelles …”
Section: Functional Handles On Polymersomes and Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…presented a similar approach for the fabrication of PEG ‐b‐ PDLLA small‐sized polymeric micelles with maleimide functional handles, which were subsequently conjugated to TAT peptides. Their in vitro and in vivo studies showed effectiveness and permeation higher than or similar to unfunctionalized cargo‐containing micelles …”
Section: Functional Handles On Polymersomes and Nanoparticlesmentioning
confidence: 99%
“…Their in vitro and in vivo studies showed effectiveness and permeation higher than or similar to unfunctionalized cargo-containing micelles. [71] Polymers which undergo topological transformations via macromolecular metamorphosis by using reversible-covalent reactive handles, capable of forming new covalent bonds in situ have been coined by Sumerlin et al. A thermodynamically selective cycloaddition between maleimide and anthracene or furan functionalized polymers allowed for metamorphosis of linear amphiphilic block-copolymers and hyperbranced polymers.…”
Section: Diels-alder and Thiol Conjugationmentioning
confidence: 99%
“…As for the TAT-PECL, the characteristic resonance of maleimide at 6.68 ppm disappeared, indicating the successful conjugation of TAT to Mal-PECL (Figure S2b, Supporting Information). [24] Besides, the appearance of the peak at 1.84 ppm in 1 H NMR of DA-TAT-PECL indicated the complete amidation of TAT amines by DA (Figure S2c, Supporting Information). [10] The signals of hydrogen protons adjacent to difsulfide bond in (CPT) 2 -ss appeared at 2.83 ppm and 4.02 ppm, while transferred to 3.08 ppm and 4.41 ppm after reaction with 2,3-dibromomaleimide (Figure S2d,e, Supporting Information).…”
mentioning
confidence: 99%
“…Loading capacity was defined as the percentage of DTX by weight in the freeze-dried nanoparticles, and encapsulation efficiency was defined as the percentage of DTX by weight incorporated in the nanoparticles compared with the initial weight of DTX (26). Both were determined by high performance liquid chromatography (HPLC) (27).…”
Section: Methodsmentioning
confidence: 99%